Reflecting on literacy methods in the construction of knowledge (Research, Society and Development, 2020)
This article was developed with the objective of understanding how the methods can contribute to the literacy process developed in the classroom, aiming, therefore, to discuss what is the best methodology to be privileged in the work done with the students of the initial grades. To support the theoretical foundations, we sought to understand the concepts of literacy, of method, as well as to discuss traditional and constructivist pedagogical trends, focusing on synthetic, analytical methods and the ideas of Paulo Freire and Emilia Ferreiro, who defend constructivist literacy. . The investigation was carried out based on observations and experiences in the classroom of the Vale do Guaporé Municipal School, located in the rural area of the municipality of Vila Bela da Santíssima Trindade-MT, where for three months the researchers observed the practices and talked with the teachers school literacy teachers. The methodological approach contemplated in the research was a qualitative investigation and a bibliographic review, which made it possible to raise information about the theme. Its theoretical framework is based on: Freire, (1980, 2000, 2001), Kato, (1999), Barbosa (1994), Silva (1981), Corrêa (2000), Soares (1998), Ferreiro (1987). Thus, the result showed evidence that good methods are fundamental in the practice of literacy, as they contribute to the students' learning. It is important to state that in addition to choosing a good method, these need to be well thought out, planned and organized, in addition to having the monitoring of children's learning. Based on the research, it was observed that it is necessary to invest in constructivist teaching methods, making it possible for literacy to be active, efficient and effectively contemplate children. In addition, the need to invest in studies and dialogues about constructivist methods is also highlighted, as teachers demonstrate weaknesses in their understanding.